(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research focuses on the effects of switching barriers and satisfaction of customer on customer loyalty in Kingdom of Bahrain’s telecommunication subscribers. For this study, a number of evidences processing techniques and instruments were used and carried out by performing a customer loyalty inquiry, a subscriber activity for the three telecommunications services companies in the Kingdom of Bahrain. The research aimed at estimating the effect of cost required to enter, interpersonal relationship, loss cost and competitiveness of substitutes such as changing barriers as well as consumer satisfaction on the retention of customers in the telecommunications services of the Kingdom of Bahrain. A study performed the efficacy of removing barriers and consumer satisfaction on customer engagement, by means of the questionnaire as the records collection mechanism. The applicants of the research study are subscribers of Batelco, Stc and Zain telecom companies in the Kingdom of Bahrain. The statistical instruments used for the study are multiple regression analysis and the Likert scale used for quantitative research to get first hand data. The study reveals that changing barriers such as cost of moving in and cost of interpersonal relationships influence customer loyalty, while attractiveness of alternative and risk of losses does not influence customer loyalty either. The study finds customer-satisfaction affects customer loyalty at the other hand. The report presents the researcher’s guidelines for evaluating certain issues around the impact of switching barriers in the telecommunications sector in the Kingdom of Bahrain. This is also proposed that in the future the relationship between breaking barriers and consumer loyalty is to be carried out in all kinds of loyalty classes. Adding more variables in this research, the researchers can make deep study in the same area.